Financial Relationships Between Pharmaceutical Companies and Rheumatologists in Japan Between 2016 and 2019. Issue 3 (7th April 2023) - Murayama, Anju; Mamada, Hanano; Shigeta, Haruki; Yoshinaga, Takamichi; Saito, Hiroaki; Yamashita, Erika; Tanimoto, Tetsuya; Ozaki, Akihiko
Abstract : Backgrounds: Given the increasing number of novel and expensive drugs for rheumatoid diseases, the financial relationships between pharmaceutical companies and rheumatologists could be prevalent and substantial. However, little was known about the information in Japan. Methods: Using payment data publicly disclosed by 92 major pharmaceutical companies, we evaluated the financial relationships between pharmaceutical companies and rheumatologists who were board certified by the Japan College of Rheumatology between 2016 and 2019. The trends in payments were estimated by the generalized estimating equations with 4-year payment data. Differences in payments between general and leading rheumatologists including the board members, clinical practice guideline authors, and medical journal editors were assessed. Results: Of the board-certified rheumatologists, 70.7% (3563 of 5038) received a total of 55, 246, 485 in personal payments for lecturing, writing, and consulting from 79 pharmaceutical companies between 2016 and 2019. The median payments per rheumatologist receiving payments were 3447 (interquartile range, 1124–11, 974) in payment amounts. There were increasing trends in the payments per rheumatologist and the number of rheumatologists with payments, with average yearly change rates of 5.9% (95% confidence interval, 3.9%–7.9%; p < 0.001) and 1.2% (95% CI, 0.3%–2.0%; p = 0.008). The leading rheumatologists such as the society board members, clinical practice guideline authors, and medical journal editors received much more payments than other rheumatologists. Conclusion: Most rheumatologists increasingly received personal payments for lecturing, consulting, and writing reimbursements from pharmaceutical companies in Japan. These payments were significantly concentrated on rheumatologists in authoritative and influential positions.